“In what way are gay men actually harmful to society?” Exploring the evidence on the feasibility of amendments to the Sexual Offences Act 23 of 1957 - Louis Grundlingh (Contree, 2011)
Prompted by a perception that a gay sub-culture developed in the major urban areas of South Africa, and that this formed a threat to state security and to the established mores of society, the Minister of Justice, PC Pelser, appointed a Parliamentary Select Committee in 1968. The essence of the task given to the Select Committee was to provide clarity to the Department of Justice about a definition of homosexual acts as well as the causes, manifestations and extent of these practices. In addition, the Committee had to ascertain whether South African society was ready to decriminalise sodomy and “unnatural” sexual practices. A major concern was whether gay men were a danger to minors. The Committee received numerous written submissions and held regular meetings to hear oral testimonies, which covered a wide spectrum of opinions and issues. Representatives of the South African Police and the Afrikaans churches vehemently opposed homosexuality and homosexual activities. Ministers from the English churches pleaded for tolerance but with very specific preconditions. The position of the lawyers, psychiatrists and psychologists was clear: that homosexuality was not a threat, could not be “cured” and should be accepted. The investigation resulted in widespread debate, revealing facets of the moral dynamics of white South African society in the 1960s. Inter alia, issues such as the right of the state to make laws on morality and intrude on the privacy of individuals, diverse interpretations of the Bible, the level of intolerance for the “other” and the apparent difficulties to enforce any amendments to the Act - as far as homosexuality was concerned - were raised. By emphasising these issues, the intention of this article is to give an indication as to what extent gay white men were tolerated. To realize this, a discussion of the context of a very strong conservative government that underpinned the activities of Select Committee was essential. The upshot was that the deep-rooted conservatism of the state prevailed, finding expression in harsher and specific measures in the Immorality Amendment Act of 1969. The strong arguments from some church representatives, as well as the medical and legal fraternities, were discarded. Clearly the time was not yet ripe for liberalising sexuality in South Africa. Research for this article relied on the extensive testimonies before the Select Commission as published in its final report. In addition, relevant submissions in the Gay and Lesbian Archive at the University of the Witwatersrand helped to form a comprehensive picture and made qualitative analysis possible.